Does default risk matter for investors in REITs - Sha, Yezhou; Wang, Zilong; Bu, Ziwen; Mansley, Nick (International Journal of Strategic Property Management, 2020)
We investigate the relationship between default risk and REIT stock returns. A default risk long-short investment strategy generates a return of 15% per annum. We also evaluate a large number of potential explanations for the negative relationship between default risk and subsequent stock returns. We do not find robust evidence that the default risk premium can be explained by firm size, book-to-market equity, asset growth and idiosyncratic volatility. However, CAPM beta shows some promise in explaining the default risk premium. Our results shed further light on the role of default risk in investment in REITs. First published online 23 September 2020